The Banana Splits movie [videorecording (DVD)] - Elinoff, Jed, 1975-; Thomas, Scott, 1975-; Kind, Dani; Wojtak-Hissong, Finlay; Carere, Romeo; Lund, Steve, 1989-; Canning, Sara, 1987-; Martin, Celina (Warner Bros. Home Entertainment, 2019)
When the infamous rock band discovers that their show is being cancelled, they violently lash out taking matters into their own hands!